Lean education in a university in the Philippines - Manalang, Anna Bella Siriban- (Animo Repository, 2016)
The De La Salle University is one of the forerunners in the introduction of Lean Manufacturing in the Philippines. The course is taught in alignment with the University’s graduate attributes, the Commission on Higher Education’s program educational objectives and the course’s required student outcomes. It is learner centered and uses project-based experiential learning. © Springer International Publishing Switzerland 2017.